1997
DOI: 10.1091/mbc.8.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular analysis of Ca2+ homeostasis in primary cultures of skeletal muscle myotubes.

Abstract: Specifically targeted aequorin chimeras were used for studying the dynamic changes of Ca2+ concentration in different subcellular compartments of differentiated skeletal muscle myotubes. For the cytosol, mitochondria, and nucleus, the previously described chimeric aequorins were utilized; for the sarcoplasmic reticulum (SR), a new chimera (srAEQ) was developed by fusing an aequorin mutant with low Ca2+ affinity to the resident protein calsequestrin. By using an appropriate transfection procedure, the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 31 publications
(63 reference statements)
2
71
0
2
Order By: Relevance
“…These cells can be easily obtained from animal models, and thus the following experiments were carried out on cells derived from neonatal rats. Muscle-derived stem cells (MDSCs) from mouse or rats can be differentiated into large myotubes, carrying most phenotypic properties of skeletal muscle in terms of contractile protein expression, morphological aspect (with diad and triad formation), and signaling properties (5).…”
Section: Adipogenic Conversion Of Muscle-derived Stem Cells On High Gmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells can be easily obtained from animal models, and thus the following experiments were carried out on cells derived from neonatal rats. Muscle-derived stem cells (MDSCs) from mouse or rats can be differentiated into large myotubes, carrying most phenotypic properties of skeletal muscle in terms of contractile protein expression, morphological aspect (with diad and triad formation), and signaling properties (5).…”
Section: Adipogenic Conversion Of Muscle-derived Stem Cells On High Gmentioning
confidence: 99%
“…Muscle-derived stem cells (MDSCs) include the so-called satellite cells, i.e., the precursor cells capable of differentiating in vivo to mature muscle fibers and in vitro up to multinucleated skeletal myotubes (5). Human satellite cells retain broad differentiation capacity, including the generation of adipocytes in appropriate culture conditions (adipogenic medium) in a process that is enhanced by the insulin sensitizer rosiglitazone (6).…”
mentioning
confidence: 99%
“…Primary cultures of MDSCs were prepared from newborn rats (2-3 days) as described in Brini et al 15 Adipogenic conversion was observed both in the first preplating (15 min) and in the replating of non-rapidly adherent cells. For this reason, the first pool of adherent cells was used for all experiments.…”
Section: Cell Cultures: Mdscsmentioning
confidence: 99%
“…The aequorin light emission was measured with a Zylox luminometer. At the end of each experiment, the total light units from the unconsumed aequorin was estimated by permeabilizing the cells with 0.5% Triton X-100 in the presence of 10 mM CaCl 2 (19,23,24). The [Ca 2ϩ ] was calculated from the value of Ϫlog(L/L max ), where L is the rate of luminescence (in arbitrary units), and L max is the rate of luminescence remaining in the sample.…”
Section: Aequorin Plasmid Amplification and Transfection Of Jurkat Cementioning
confidence: 99%